‘Taking Fishers’ Knowledge to the Lab’: An Interdisciplinary Approach to Understand Fish Trophic Relationships in the Brazilian Amazon - Pereyra, Paula Evelyn Rubira; Hallwass, Gustavo; Poesch, Mark; Silvano, Renato Azevedo Matias (Frontiers in Ecology and Evolution, 2021)
Trophic levels can be applied to describe the ecological role of organisms in food webs and assess changes in ecosystems. Stable isotopes analysis can assist in the understanding of trophic interactions and use of food resources by aquatic organisms. The local ecological knowledge (LEK) of fishers can be an alternative to advance understanding about fish trophic interactions and to construct aquatic food webs, especially in regions lacking research capacity. The objectives of this study are: to calculate the trophic levels of six fish species important to fishing by combining data from stable isotopes analysis and fishers’ LEK in two clear water rivers (Tapajós and Tocantins) in the Brazilian Amazon; to compare the trophic levels of these fish between the two methods (stable isotopes analysis and LEK) and the two rivers; and to develop diagrams representing the trophic webs of the main fish prey and predators based on fisher's LEK. The fish species studied were Pescada (Plagioscion squamosissimus), Tucunaré (Cichla pinima), Piranha (Serrasalmus rhombeus), Aracu (Leporinus fasciatus), Charuto (Hemiodus unimaculatus) and Jaraqui (Semaprochilodus spp.). A total of 98 interviews and 63 samples for stable isotopes analysis were carried out in both rivers. The average fish trophic levels did not differ between the stable isotopes analysis and the LEK in the Tapajós, nor in the Tocantins Rivers. The overall trophic level of the studied fish species obtained through the LEK did not differ from data obtained through the stable isotopes analysis in both rivers, except for the Aracu in the Tapajós River. The main food items consumed by the fish according to fishers’ LEK did agree with fish diets as described in the biological literature. Fishers provided useful information on fish predators and feeding habits of endangered species, such as river dolphin and river otter. Collaboration with fishers through LEK studies can be a viable approach to produce reliable data on fish trophic ecology to improve fisheries management and species conservation in tropical freshwater environments and other regions with data limitations.